The Holy Qur'an (3GdbQGAf GdcQje (B/s - Harf Information Technology (Egypt : Harf Information Technology, 2000)
The Arabic text of the Qur'an is displayed in Uthmanic Calligraphy together with a practical explanation of the rules of recitation and the places of articulation of Arabic letters. The program offers accurate textual search for words using advanced computational linguistic analysis technology. Topical search by the means of a subject tree, subdivided into more than two thousand subjects, is also available to the user.
Holy Qur'an v7.10 (software CD)
System requirements : Windows 95, 98, 2000
Translation text available in Arabic / English / Malay / Indonesian
Keywords: Qur'an -- Study and teaching